Uji Daya Hambat Senyawa Xylitol dari Limbah Tongkol Jagung pada Bakteri Streptococcus Mutans - Mahyati, Mahyati (INTEK: Jurnal Penelitian, 2017)
Corncob contains xylan content of 12.4 - 12.9% which can be converted to xylitol [1]. Xylitol significantly reduces the population of Streptococcus mutans (S. mutans) in saliva compared with fluoride [3]. The effectiveness of xylitol from corn cobs waste is an antibacterial substance of S. mutans in safe and water-soluble mouthwash. The purpose of this research is to produce xylitol from corn cobs waste and to test the xylitol inhibition as anti bacterial in S. mutans bacteria. The xylitol extraction method of corncob using aqueous sulfuric acid is 0.25; 0.5; 0.75 and 1.0%. The extraction time was then varied from 15, 30, 45, 60, 75 and 90 min. The results showed xylitol compound from corn tuna waste was highest at 0.25% sulfuric acid concentration with 30 minutes hydrolysis time of 249.7 ppm and the lowest at 0.75% acid concentration and hydrolysis time of 90 minutes is 5.6 ppm. Xylitol compounds can be obtained from corn cobs waste has the value of inhibitory growth of S. Mutans bacteria in all variations of acid concentration (H2SO4) and hydrolysis time is 100%.